KUATNYA KEKUASAAN ONDOAFI DI TENGAH MASYARAKAT URBAN (Studi Tentang Kekuasaan Ondoafi di Kota Jayapura Papua) - BONEFASIUS BAO, BONEFASIUS BAO (Politika: Jurnal Ilmu Politik, 2010)
AbstractThis paper aims to find out Ondoafi in the capital to actualize its power, and care for it so thepower of capital in the middle of an urban community. The result can understand the practice ofpower in traditional society is changing.There are three power capital Ondoafi namely social capital, symbolic and material. Assumingthe persistence of capital even living in urban areas had to survive because they have the ability tomanage symbols, manage social relationships and manage the economy. Allegations were provenbecause of the discussion about the workings of the three capital Ondoafi power, can be in the knowthat Ondoafi respond to change with the actualization of such capital through a revitalization strategy,adaptation and repositioningThose capitals is not working alone but comes along. Ondoafi convert into equity capital oneanother so that there is a logical relationship with his rule. Capital-capital is reproduced andexchanged with each other. In practice the power to show how the three capital Ondoafi able tomanage its power to make strategic changes. Ondoafi thus becomes very important and strategic foranyone who needs it.Keyword : power, revitalitation, adaptation, reposition.